2012
DOI: 10.1073/pnas.1219899110
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial drug leads targeting isoprenoid biosynthesis

Abstract: With the rise in resistance to antibiotics such as methicillin, there is a need for new drugs. We report here the discovery and X-ray crystallographic structures of 10 chemically diverse compounds (benzoic, diketo, and phosphonic acids, as well as a bisamidine and a bisamine) that inhibit bacterial undecaprenyl diphosphate synthase, an essential enzyme involved in cell wall biosynthesis. The inhibitors bind to one or more of the four undecaprenyl diphosphate synthase inhibitor binding sites identified previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
164
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 92 publications
(170 citation statements)
references
References 31 publications
6
164
0
Order By: Relevance
“…In recent work, we (49) and others (50, 51) identified several anionic, bacterial cell growth inhibitors that, in addition to inhibiting bacteria-specific enzyme targets, might have activity as uncouplers, as expected for lipophilic, weak acid, classic uncouplers like CCCP and DNP. We first investigated seven compounds with known antibacterial activity and a diverse range of proposed protein targets.…”
Section: Resultsmentioning
confidence: 55%
“…In recent work, we (49) and others (50, 51) identified several anionic, bacterial cell growth inhibitors that, in addition to inhibiting bacteria-specific enzyme targets, might have activity as uncouplers, as expected for lipophilic, weak acid, classic uncouplers like CCCP and DNP. We first investigated seven compounds with known antibacterial activity and a diverse range of proposed protein targets.…”
Section: Resultsmentioning
confidence: 55%
“…Recently, several studies have shown that bacterial UPPS is an attractive antibiotic target (4,88) and that inhibitors of UPPS are protective in a mouse model of infection (89). Based on the experimental data concerning G. lamblia cis-PT and phylogenetic analysis of cis-PT from Trypanosoma sp., Leishmania sp., and Plasmodium sp., we predict that targeting protozoan cis-PT may also be a reasonable strategy to treat and control infections such as malaria, sleeping sickness, Chagas disease, leishmaniasis, and intestinal infections.…”
Section: Genetic Validation Of Two-component Ngbr/hcit Complex In Humansmentioning
confidence: 99%
“…Four subsequent steps lead to the synthesis of IPP and DMAPP, the universal precursors to FPP. The synthesis of undecaprenyl pyrophosphate in bacteria originates from all-trans-FPP by the addition of eight isopentenyl units catalysed by the soluble enzyme undecaprenyl pyrophosphate synthase UppS (Guo et al, 2005;Teng & Liang, 2012a, b;Zhu et al, 2013). Undecaprenyl pyrophosphate and dolichol de novo synthesis are distinguished by terminal products (an isoprenyl pyrophosphate versus an alcohol) as well as the saturation state of the a-isoprene units (unsaturated versus saturated).…”
Section: Biosynthesis Of the Eubacterial Undecaprenyl Lipid Carriersmentioning
confidence: 99%